Staphylococcus aureus Genotypes of Subclinical Bovine Mastitis Milk in the Middle Western Anatolia - Kanber, Gülgün; Kenar, Beytullah; Güven, Kiymet (Journal of Buffalo Science, 2018)
Background: Staphylococcus aureus is the most common etiological pathogen of bovine mastitis. Subclinical mastitis is characterised by a non-alteration of the milk but can cause food poisoning by production of enterotoxins in milk. Knowledge about the genetic variability within different S. aureus populations would help in the design of efficient treatments to prevent subclinical mastitis and provide useful data for epidemiological studies. The aim of this study was to characterize the genetic nature of the S. aureus cultured from subclinical bovine mastitis occurring in 16 farms in the middle western Anatolia. Methods: Two hundred sixty eight milk samples positive with California Mastitis Test (CMT) suggesting the subclinical mastitis of lactating cows in 16 different farms in the Middle Western Anatolia were collected and S. aureus were isolated. Identification was carried out by traditional tests and ribotyping confirmed the identification. Staphylococcal Enterotoxins (SE) were detected and typed by Staphylococcal Enterotoxin Test Reversed Passive Latex Agglutination (SET-RPLA) test kit. Genetic characterisation of the isolates was carried out by both ribotyping and pulsed field gel electrophoresis (PFGE). Results: A total of 77 isolates of S. aureus were purified and analysed by both biochemical identification and genotyping. Only 4 isolates (5.19 %) of S. aureus were recorded as enterotoxin positive. Genetic characterisation of the isolates was carried out by ribotyping revealed eight ribotypes while pulsed field gel electrophoresis (PFGE) was more discriminative representing 19 pulsotypes. Conclusion: This study shows no significant association between enterotoxin production, ribogroup and pulsotype profile of the S. aureus isolates collected from the Middle Western Anatolia.